Numerical modelling of wind-influenced above sea gas dispersion and explosion risk analysis due to subsea gas release on multileveled offshore platform - Malik, A.A. (Elsevier Ltd, 2022)
Above-sea gas dispersion due to subsea release could lead to explosion on nearby offshore facility. Less congested single-deck offshore platform has been considered in past for numerical modelling of above-sea gas dispersion and deflagration. Offshore platforms are designed compactly and comprise of multiple decks due to space restrictions. The approaching flammable gas may disperse differently at each deck, and high overpressures could develop in event of explosion in confined decks causing severe damages. Therefore, investigating effect of above-sea gas release and dispersion and resulting vapour cloud explosion on equipment damage and human fatality in complex multi-deck platform is worth investigating. This paper presents above-sea gas dispersion and explosion modelling on realistic multileveled fixed offshore platform under varying wind speeds using FLACS. Simplified steps are provided to model gas release from large area sea surface gas pool along with atmospheric dispersion and subsequent explosion in FLACS. It was found that generally, lower decks had near-stoichiometry concentrations thus being most susceptible to explosion consequences. High wind speed increased flammable cloud accumulation, where 50-60 of decks were filled at 3m/s wind speed whereas 100 filled under 7m/s. It is suggested to have adequate ventilation on lower platform decks specially under high wind circumstances to avoid possible explosion hazard due to cloud accumulation. Congested and confined regions with low flammable concentration produced more overpressure than the areas with same concentration but no or low congestion and confinement. Stoichiometric concentration together with congestion produced incredibly high localised overpressure reaching 3.55-4 barg. The probability of equipment damage and human fatality was reaching 1 for explosions at base and deck 2 under 7 m/s wind speed. Since roof was open, the probability of equipment damage and human fatality was least. Â© 2022 Elsevier Ltd